2017
DOI: 10.18646/2056.43.17-012
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Mobile Learning Conceptual Framework for Professional Development of UAE In-Service Teachers

Abstract: Increasingly, mobile learning has been considered as a part of professional development due to its unique attributes: ubiquitous, flexible, highly personalized and easily accessible. It represents a paradigm shift for continuous professional development especially amongst teachers who have a tight working schedule. This paper will provide a conceptual framework for the design of a mobile learning course for UAE teachers' professional development. It aims to assist teachers to continuously engage in professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…In the UAE, mobile learning technology in teaching foreign languages also has its characteristics and differences from the Russian experience. Some researchers believe that m-learning is inextricably linked to professional development and focuses on the availability of educational videos, gamification of content, and easy navigation necessary for effective learning [32]. According to researchers, in the Arab states of the Persian Gulf, UAE students have a more positive attitude towards the use of mobile applications to learn foreign languages in general and EFL in specific, compared to students in Oman; 81.5% of Arab students use mobile devices in their studies while only 18.5% do not [33].…”
Section: Features Of Using Mobile Applications In Different Countriesmentioning
confidence: 99%
“…In the UAE, mobile learning technology in teaching foreign languages also has its characteristics and differences from the Russian experience. Some researchers believe that m-learning is inextricably linked to professional development and focuses on the availability of educational videos, gamification of content, and easy navigation necessary for effective learning [32]. According to researchers, in the Arab states of the Persian Gulf, UAE students have a more positive attitude towards the use of mobile applications to learn foreign languages in general and EFL in specific, compared to students in Oman; 81.5% of Arab students use mobile devices in their studies while only 18.5% do not [33].…”
Section: Features Of Using Mobile Applications In Different Countriesmentioning
confidence: 99%
“…Seventeen studies [6], [53], [54], [55], [44], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], and [67] mentioned challenges related to adapting and appropriating mobile learning technology to learn in a compatible way with suitable learning theories, objectives and actual training/learning needs. The remaining twenty-four studies [6], [68], [69], [70], [71], [72], [10], [73], [37], [74], [1], [8], [75], [16], [76], [38], [45], [77], [78], [79], [12], [80], [81], and [82] confirmed the existence of challenges related to a lack of implementation and development of effective methods for designing mobile training/learning content, such as the use of pedagogical models, frameworks or learning strategies. These represented the majority of the 50 studies that mentioned pedagogical challenges, and this is therefore considered to be the most significant pedagogical challenge in the design of mobile training content.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the design of compatible, user-friendly, attractive and interactive content to increase both the engagement of learners with mobile training courses and these courses' accessibility to trainees is different from designing electronic training courses to be used on a mobile device, such as designing a web-based (online) course to be accessed via an internet browser by using a mobile device. Instructional design is considered to be one of the most important issues for designing mobile training content, and it is linked to learning theories that represent the main role for designing mobile training content as a foundation for a pedagogical theory that enhances the development of mobile learning courses [8]. Moreover, designers should consider the limitations of mobile devices, such as the monitor size, input devices, navigation and challenges in bandwidth during browsing, when designing mobile learning content [6].…”
Section: Figure 1 Advantages and Benefits Of Mobile Trainingmentioning
confidence: 99%
See 2 more Smart Citations